Estetyczne wywody użytkowników Internetu na temat interpretacji muzycznych podczas Konkursu Chopinowskiego w 2015 roku = The aestheticcomments of Internet users on the interpretationsduring the Chopin Competition in 2015 - Kładoczny, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns Internet users` opinions on the performances of the participants of the 17th Chopin Competition in 2015. The material comes from two sources: the Audio.com. pl online forum and the profile on Facebook. All the statements are neutral in terms of the aesthetics of expression, they do not contain elements of hate or profanity, but they are not built as stylized or artistic.
Keywords: 17 Konkurs Chopinowski; estetyka; metafora; internet; język; synestezja; 17th Chopin Competition; aestetics; language; metaphor; synesthesia